2009
DOI: 10.1089/ars.2008.2248
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol Is Ineffective in Preventing the Decomposition of Preformed Lipid Peroxides and May Promote the Accumulation of Toxic Aldehydes: A Potential Explanation for the Failure of Antioxidants to Affect Human Atherosclerosis

Abstract: The decomposition of peroxidized lipids of low-density lipoprotein (LDL) has been suggested to be involved in atherosclerosis. In this study, an in vitro system with 13-hydroperoxylinoleic acid (13-HPODE) was used to determine the effects of antioxidants on its decomposition. Decomposition of 13-HPODE was not affected by a-tocopherol, several other antioxidants, or antioxidant enzymes. Moreover, the inclusion of a-tocopherol during the decomposition of 13-HPODE resulted in an accumulation of aldehydes. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…RPMI-1640, FBS, penicillin-streptomycin, 1× PBS, NBD Cholesterol (22- TLC using hexane-diethyl ether-acetic acid (30:6:0.5, v/v/v) solvent system, and visualized with iodine vapors ( 35 ). Bands were identifi ed by comparing with authentic standards, and TLC spots corresponding to cholesterol and CE were analyzed with liquid scintillation counter (MicroBeta2 Plate Counter; PerkinElmer).…”
Section: Reagentsmentioning
confidence: 99%
“…RPMI-1640, FBS, penicillin-streptomycin, 1× PBS, NBD Cholesterol (22- TLC using hexane-diethyl ether-acetic acid (30:6:0.5, v/v/v) solvent system, and visualized with iodine vapors ( 35 ). Bands were identifi ed by comparing with authentic standards, and TLC spots corresponding to cholesterol and CE were analyzed with liquid scintillation counter (MicroBeta2 Plate Counter; PerkinElmer).…”
Section: Reagentsmentioning
confidence: 99%
“…Supplementation of antioxidant vitamins such as -tocopherol, ascorbic acid and -carotene used alone or in combination had long been considered to be cardio protective. However, controlled clinical trials using antioxidant vitamin supplements to prevent CVD have yielded conflicting results (Raghavamenon et al, 2009). While some secondary prevention interventions have been shown with -tocopherol supplementation alone or in combination with ascorbic acid is reported to reduce CVD risk, other studies have shown no effect oftocopherol supplementation in both primary and secondary prevention.…”
Section: Benefits Of Antioxidants Against Lipid Peroxidationmentioning
confidence: 99%
“…In such cases, -tocopherol and similar antioxidants could affect the conversion of aldehydes into carboxylic acids. The latter, are presumed to be nonatherogenic and are easily degraded via fatty-acid degradation pathways (Raghavamenon et al, 2009). Based on these arguments it may be necessary for the scientific community to revisit the topic and investigate in well structured studies the type, dose, duration of the anitoxidants on a well defined population of subjects with various stages of CVD and its associated metabolic disorders such as diabetes, obesity and hyperlipidemia.…”
Section: Clinical Studies: Oxldl and Antioxidantsmentioning
confidence: 99%
“…In a number of works a clear correlation between the HL activity and the LDLB content in the blood plasma was demonstrated [19]. It is believed that namely HL activation results in the increased LDLB formation [33].…”
Section: Discussionmentioning
confidence: 98%
“…Stress was caused by immobilization on the abdomen for 3 hours [19]. Animals were decapitated 3 hours after the immobilization.…”
Section: Experiments Designmentioning
confidence: 99%